Cost-driven provisioning and execution of a computing-intensive service on the Amazon EC2. (2nd February 2018) - Álvarez, Pedro; Hernández, Sergio; Fabra, Javier; Ezpeleta, Joaquín
Abstract: The decision of migrating a service to a cloud-based system must take into consideration many different aspects. Among them, economical costs is one of the most important. This paper describes how a computing-intensive service, based on a bag-of-tasks approach, has been migrated from a grid infrastructure to the Amazon Elastic Compute Cloud (EC2) infrastructure. A cost-based model for the evaluation of the economic costs of providing the service on the cloud has also been proposed, which considers computing costs as well as storage and platform deployment costs. The model includes a wide range of different instance types and purchasing policies provided by the Amazon EC2, as well as the deadline and problem size provided by the service user. The paper also shows how the proposed cost-based model is integrated into the framework used for the service deployment and execution, making possible the interaction with the Amazon Web services for hiring the required cloud resources and efficiently use them for the execution of the service requests.